UPAYA MENINGKATKAN KEMAMPUAN MENGHITUNG PENJUMLAHAN MATERI PECAHAN PADA MATA PELAJARAN MATEMATIKA KELAS IV MELALUI METODE NUMBERED-HEAD TOGETHER (NHT) DI MI ISLAMIYAH SIDOARJO - Rohmawati, Rohmawati (Journal Of Islamic Elementary School (JIES), 2017)
Fourth grade students of MI Islamiyah Sidoarjo have difficulty in calculating the addition of fractions in mathematics. In learning mathematics, teachers often use traditional methods, namely, lectures and questions and answers only. So, students look passive and play alone during the learning process. So that the ability of students in calculating the addition of fractions is still low. We can see this from the results of the ability to learn mathematics in the fractional addition material that was not maximized at the time of the pre-cycle, which was only 7 students who completed out of 31 students with a KKM of 80. One of the alternatives used to overcome the low results of students’ abilities was using the Numbered Head Together method. (NHT). The purpose of this study was to determine the application of the Numbered Head Together (NHT) method in mathematics subjects for fourth grade students of MI Islamiyah Sidoarjo and to determine the increase in the ability to calculate the addition of fractions in mathematics subjects using the Numbered Head Together (NHT) method in fourth grade students. MI Islamiyah Sidoarjo. This study uses Kurt Lewin’s class action research model which was carried out in two cycles to determine the increase in the ability to calculate the addition of fractions through the NHT method. Which consists of four stages, namely planning, implementation, observation, and reflection. The target of this research is fourth grade students at Madrasah Ibtidaiyah Islamiyah Sidoarjo. With a total of 31 students consisting of 18 students and 13 students. The data collection used in this study were interviews, teacher and student observations, tests, and documentation. From the results of this analysis, it can be seen that the application of the Numbered Head Together (NHT) method for fourth grade students of MI Islamiyah Sidoarjo can increase the activity of teachers and students in learning mathematics, it can be seen in the first cycle of teacher observations 81.25 and students 72.54 while in the second cycle teacher observations 89.58 and students 96.08. The increase in the ability to calculate the addition of fractions for fourth grade students of MI Islamiyah Sidoarjo in the fractional material increased. This can be seen in the percentage of completeness improvement in the ability to calculate the addition of fractions of students in the first cycle reaching 48.27% with an average value of 64.45, while in the second cycle it reaches 77.42% with a class average of 83.45.